'Hey, I like ur videos. Super relate!' Locating sisterhood in a postcolonial intimate public on YouTube. Issue 6 (11th May 2020) - Cabalquinto, Earvin Charles; Soriano, Cheryll Ruth R.
ABSTRACT: This paper re-examines YouTube as a site of feminine, networked, and intimate sociality among Filipino women online. We unpack this by identifying how commenters on YouTube engage with the performativity of an intimate relationship between a Filipina and her foreign husband on YouTube. Extending Mina Roces' concept of 'local sisterhood' in the digital context, we coin the term 'online sisterhood' to articulate the diverse ways through which Filipino women engage with interracial intimacies in the realm of online communication. By conducting a thematic analysis of comments on a popular YouTube channel of a Filipina married to a Caucasian man, we uncover the dimensions of an unfolding online sisterhood as aspirational, relatable, regulatory, and defensive modalities. We argue that these frames are informed by gendered, racialized and even class-based aspirations and contestations tied to Philippine postcolonial history and society. Ultimately, as a site for feminine sociality and intimacy, YouTube also becomes an avenue for constructing, reinforcing and countering the stereotypical representations of Filipino women in a networked and postcolonial space.